Neurological ct Scan Value for Ictus in Cienfuegos Province - Idaylí Pérez Rodríguez; Dianarelys Villafuerte Delgado; Rubén Bembibre Taboada; Adelaida Martínez Godoy; José Roque Nodal (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2007)
Backgrounds: CT scan constitutes a very important technique in the diagnosis of the cerebrovascular disease. The impact this transcendental event had and will continue having in the medicine area is impossible to state in terms of dimensions during the next years. Objective: To determine the neurological CT scan value for ictus in our milieu. Methods: A retrospective, prospective, longitudinal study of a series of cases performed during a review of statistical reports as well as that of Stroke data base which stores information of patients with neurocitus in our province, and which is based on others aspects founds by means of neurological CT scan. Results: CT scan allowed us to diagnose the type of cerebrovascular event (75.55 % ischemic events, 24.45% hemorrhagic events). It also contributed to the necessary data such as the localization (with predominium of 35.55% in more than one area, and 7.40 % in the parietal area. The presence of cerebral edema was verified in 16.29% of the cases as well as displacement of the midline in 7.40 % both associated to a torpid evolution. It incorporated the Fisher and Le Roux scales showing their prognosis value with elevated measures for deceased patients and decreased values for survivors without disability. Conclusions: The diagnosis and prognosis value were proved as well as CT scan behavior in our milieu. These aspects permit the reliable introduction of new therapeutic modalities in our province.